Exploring How Adipose Tissue, Obesity, and Gender Influence the Immune Response to Vaccines: A Comprehensive Narrative Review - De Sanctis, Juan Bautista; Balda Noria, Germán; García, Alexis Hipólito (International journal of molecular sciences, 2025)
Vaccines represent an essential tool for the prevention of infectious diseases. Upon administration, a complex interaction occurs between the vaccine formulation and the recipient's immune system, ultimately resulting in protection against disease. Significant variability exists in individual and population responses to vaccination, and these differences remain the focus of the ongoing research. Notably, well-documented factors, such as age, gender, and genetic predisposition, influence immune responses. In contrast, the effects of overweight and obesity have not been as thoroughly investigated. The evidence indicates that a high body mass index (BMI) constitutes a significant risk factor for infections in general, with adipose tissue playing a crucial role in modulating the immune response. Furthermore, suboptimal levels of vaccine seroconversion have been observed among individuals with obesity. This review provides a plausible examination of the immunity and protection conferred by various vaccines in individuals with an overweight status, offering a comprehensive analysis of the mechanisms to enhance vaccination efficiency.
Keywords: Animals; Female; vaccine response; vakcíny; immune response; ženské pohlaví; thyroid hormones; vakcinace; Obesity; lidé; recombinant vaccines; Vaccines; mRNA vaccines; Humans; Sex Factors; Vaccination; obezita; Male; gender; sexuální faktory; index tělesné hmotnosti; inactivated vaccine; tuková tkáň; zvířata; mužské pohlaví; adipokines; Body Mass Index; obesity; Adipose Tissue